Application of Blockchain Technology in Carbon Trading Market: A Systematic Review - Timileyin P. Abiodun; Nnamdi I. Nwulu; Peter O. Olukanmi (IEEE Access)
The carbon trading system is a mechanism that employs carbon caps (limits) and taxation to regulate the rate of carbon dioxide emissions produced by human activities. To further strengthen the effectiveness of this mechanism, the United Nations (UN) initiated the Kyoto Protocol in 1997, enabling the trading of carbon emission rights in exchange for financial compensation. As a result, the market value rose to 10.9 billion in 2005, with an annual growth rate of approximately 8%, reaching 95 billion in 2023. Despite this expansion, the system’s management has remained centralised since its inception, leading to issues such as a lack of transparency and openness in the trading process, inefficiencies in the trading mechanisms, and inaccurate or dishonest centralised data recording. The rapid expansion of the market and the accompanying challenges underscore the need for blockchain technology (BCT), which offers a decentralised, secure, and tamper-proof system. Although several research publications have demonstrated the potential enhancements that BCT could contribute to the carbon market, no systematic review has yet examined the optimal implementation of BCT within the context of carbon trading and taxation. This study, therefore, undertakes a systematic review of peer-reviewed research articles published between 2015 and 2023 using the PRISMA methodological framework. Our analysis establishes the feasibility and viability of a blockchain-powered solution for carbon trading, alongside the development of a comprehensive framework for its effective implementation, designed to stand the test of time in the fast-evolving technological landscape. Furthermore, this comprehensive review identifies research gaps, offering future researchers direction in exploring blockchain applications within the Emissions Trading System (ETS) domain. Overall, this review fosters a digitalised and incentivised shift towards renewable energy sources.